2021
DOI: 10.3389/fcimb.2021.751947
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans as an Infection Model for Pathogenic Mold and Dimorphic Fungi: Applications and Challenges

Abstract: The threat burden from pathogenic fungi is universal and increasing with alarming high mortality and morbidity rates from invasive fungal infections. Understanding the virulence factors of these fungi, screening effective antifungal agents and exploring appropriate treatment approaches in in vivo modeling organisms are vital research projects for controlling mycoses. Caenorhabditis elegans has been proven to be a valuable tool in studies of most clinically relevant dimorphic fungi, helping to identify a number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 113 publications
(144 reference statements)
0
6
0
2
Order By: Relevance
“…We observed that Cdc50 is associated with cell wall integrity, which is of vital importance of fungal virulence; therefore, we carried out C. elegans survival assays to estimate the overall virulence of the Δcdc50 mutant in vivo. As a classical model organism that feeds on microorganisms, C. elegans is often used to evaluate the virulence of fungal and bacterial pathogens [ 44 ]. Over 300 C. elegans were transferred to plates containing medium supporting C. glabrata growth, which were incubated for at least 25 days, during which the death count of each group was recorded daily to construct the survival curve shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that Cdc50 is associated with cell wall integrity, which is of vital importance of fungal virulence; therefore, we carried out C. elegans survival assays to estimate the overall virulence of the Δcdc50 mutant in vivo. As a classical model organism that feeds on microorganisms, C. elegans is often used to evaluate the virulence of fungal and bacterial pathogens [ 44 ]. Over 300 C. elegans were transferred to plates containing medium supporting C. glabrata growth, which were incubated for at least 25 days, during which the death count of each group was recorded daily to construct the survival curve shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NC Negative control. *, P < 0.05; **, P < 0.01 the virulence of fungal and bacterial pathogens [44]. Over 300 C. elegans were transferred to plates containing medium supporting C. glabrata growth, which were incubated for at least 25 days, during which the death count of each group was recorded daily to construct the survival curve shown in Fig.…”
Section: The δCdc50 Mutant Shows Weakened Virulence Toward Caenorhabd...mentioning
confidence: 99%
“…Mantarlarda dimorfizmin virülansa etkisi iyi bilinmekte (17,18) , Mucorales için dimorfizm ve virülans arasındaki ilişki de açıklanmaktadır (19) . M. circinelloides'in küf ve maya dönüşümünü belirleyen faktörler bilinmektedir.…”
Section: Discussionunclassified
“…M. circinelloides'in küf ve maya dönüşümünü belirleyen faktörler bilinmektedir. Karbon kaynağı olarak fermente edilebilir heksoz şeker var ise, maya formu gelişirken, karmaşık karbon kaynakları varlığında küf formu gelişmiştir (19) . Oksijene bağlı dimorfizm gösteren bu mantarın maya formunun elde edilmesi için anaerobik ortam koşulları oda sıcaklığı hazırlanmıştır ve 96 saat sonunda istenilen küf-maya dönüşümü gerçekleştirilmiştir.…”
Section: Discussionunclassified
“…Regarding fungi, studies have centered on nematode infections induced by dimorphic fungi, yeast-like fungi such as C. neoformans and C. albicans , and filamentous fungi like A. fumigatus and Drechmeria coniospora , which commonly inhabit natural settings [ 123 , 130 , 131 , 132 , 133 , 134 , 135 ]. Consequently, C. elegans has become an extensively explored in vivo model for investigating human infections caused by pathogens [ 123 , 124 , 135 , 136 ].…”
Section: The Caenorhabditis Elegansmentioning
confidence: 99%